Verification environments for USB controller - Zargaryan, Grigor Y. (Изд-во НАН РА)
The complexity of electronic devices with the everyday growing requirements is constantly increasing. Sowtfare/Hardware (SW/HW) integration, validation and reducing time to market have become one of the major bottlenecks in the design and verification flow. This paper presents the main ways of design and verification flows with their advantages and disadvantages for USB 3.0 controller. It discusses the design flow with the combination of simulation and prototype-based design and presents а simulation-based verification and also two types of field-programmable gate array (FPGA) based verification environments with their advantages and disadvantages. The design done with this flow will enable system on a chip (SoC) designers to develop a high-quality USB 3.0 silicon solution to meet the growing market demands in a timely manner.
Keywords: Mathematics; Computer software